Inovasi Pembelajaran Digital: Peran Chromebook dalam Meningkatkan Keterlibatan Siswa dalam Pembelajaran IPA - Majidatun Ahmala; Lisa Amelia (Pascasarjana Universitas Qomaruddin, 2025)
In science learning in Grade V at SD Negeri 01 Sumber Harapan, there is an issue regarding the lack of student engagement in the learning process. Students tend to be passive and unenthusiastic about participating in class activities. This issue arises due to the teacher’s limited use of technology during instruction. To address this problem, the integration of technology such as Chromebooks is considered a strategic step aligned with 21st-century educational needs.The purpose of this study is to examine whether the use of Chromebooks in learning can enhance student engagement, particularly in the topic of the human skeletal system, among fifth-grade students at SD Negeri 01 Sumber Harapan. This research uses a descriptive qualitative approach. The main focus is to describe the implementation process of Chromebook-based science learning in Grade V and to analyze the forms of student engagement during the learning process.The study was conducted at SD Negeri 01 Sumber Harapan, involving fifth-grade teachers and students in the 2024/2025 academic year as research subjects. Data collection techniques included indirect observation, interviews, and documentation. Indirect observation was conducted by analyzing video recordings of classroom instruction carried out by the teacher. These videos captured the entire learning process using Chromebooks, including the introduction, core activities, and closing stages. Semi-structured interviews were conducted with the fifth-grade teacher and several students. Documentation was carried out by collecting and analyzing materials related to the implementation of Chromebook-based learning. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study show that the teacher utilized Chromebooks effectively in fifth-grade science lessons, which led to increased student engagement. The improvements observed include: (1) students were able to explore learning materials independently, (2) students showed increased confidence in expressing their opinions, and (3) students actively participated in group project work.